Cross‐sectional analysis of the Myasthenia Gravis Patient Registry: Disability and treatment. Issue 6 (9th October 2019) - Cutter, Gary; Xin, Haichang; Aban, Inmaculada; Burns, Ted M.; Allman, Phillip H.; Farzaneh‐Far, Ramin; Duda, Petra W.; Kaminski, Henry J.
Abstract: Introduction: The Myasthenia Gravis Patient Registry (MGR) is a voluntary, patient‐submitted database dedicated to improve understanding of care/burden of myasthenia gravis (MG). Methods: In this study we present analyses of baseline records through July 2017 (n = 1140) containing data on the MG—Activities of Daily Living (MG‐ADL) and the MG 15‐item Quality of Life (MG‐QOL15) instruments, two validated scales assessing quality of life in MG patients at sign‐up into the MGR. Results: Most registrants reported moderate to severe impairment of health‐related quality of life, with a median MG‐ADL score of 6 and a median MG‐QOL15 score of 21. Seventy‐one percent of the patients had received pyridostigmine. Corticosteroids, mycophenolate mofetil, and azathioprine were the most common immunomodulators/immunosuppressants, with 85% of participants having ever using one of these agents. Forty‐seven registrants reported receiving intravenous immunoglobulin, and 30% received plasma exchange. Twelve percent reported other treatments, and 40% were unsure whether they received less common therapies. Forty percent had undergone thymectomy. Discussion: The MGR data correlate well with other MG cohorts. Many MG patients remain negatively impacted despite treatment.